INTERAKSI DEWAN KOMISARIS INDEPENDEN DENGAN KINERJA KEUANGAN TERHADAP INCOME SMOOTHING (STUDY PADA PERUSAHAAN PROPERTY DAN REAL ESTATE) - Parningotan Sianturi, Jepri; Suratno; Mulyadi (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
The purpose of this study is to test whether the variable profitability and financial leverage affect the practice ofincome smoothing, and test whether the variable profitability and financial leverage moderated by the board ofindependent commissioners affect the practice of income smoothing. The population in this study are all propertyand real estate companies listed on the Indonesia Stock Exchange, while the object of research (samples) as manyas 158 data. The technique of determining the sample using purposive sampling method. Data were tested usingbinary logistic regression. The result of the research shows that profitability has significant effect to incomesmoothing, financial leverage has no effect on income smoothing, profitability moderated by independent board ofcommissioner has significant negative effect to income smoothing, and financial leverage moderated by independentboard of commissioner has no effect to income smoothing.